(untitled) (Historia, 2021)
Thirdly, the book is an object lesson in presenting research results. On of this book’s more important methodological contributions is that it shows us how a subject far removed from us in cultural time-space can be integrated into our own lifeworlds and made familiar. Using a calendar and the very same months we live by is the most obvious way of connecting the middle ages with the reader’s cultural world, as is the consideration of what people expected of the end of the first millennium. Archbishop Wulfstan of York’s reputation and social role must become clear to anybody over forty who reads that Wulfstan was “... the Billy Graham of the year 1000, whose fire-and-brimstone sermons had folk trembling.” (p.48) The point of all this is that solid research can be presented in a light-hearted way and with contemporary allusions and similes. Indeed, this kind of approach adds value to the research by making it accessible and meaningful to a larger circle of readers. Lastly, although The year 1000 consists largely of interesting but apparently trivial snippets of unconnected information, It is not merely an antiquarian compilation: the book has structure and purpose that gives it existential relevance. In their conclusion Lacey and Danziger declare that: “Whether we today display more wisdom or common humanity is an open question, and as we look back to discover how people coped with the daily difficulties of existence a thousand years ago, we might also consider whether, in all our sophistication, we could meet the challenges of their world with the same fortitude, good humour, and philosophy.” (p.201)